ANALISIS PROSES BERPIKIR REFLEKTIF DALAM PEMECAHAN MASALAH MATEMATIKA DI TINJAU DARI GAYA BELAJAR SISWA - Ninda Yulia Sari; lailatul Mubarokah; Dewi Sukriyah (JEDMA Jurnal Edukasi Matematika, 2021)
This study aims to analyze students' reflective thinking processes in solving mathematical problems in terms of learning styles. This research is a descriptive qualitative research that describes reflective thinking in problem solving in terms of learning styles. This study used eight subjects with two learning styles each. The data collection technique in this study was carried out by means of tests and interviews. The results showed that the subject took complete problem solving steps, meaning that the subject took steps in the reflective thinking process. Reflective thinking process in solving mathematical problems in terms of accommodator learning style has not been carried out properly because it did not carry out the test and information of conclutin stage. Reflective thinking process in solving mathematical problems in terms of diverger learning styles has not been carried out properly because it does not carry out the rational elaboration of an idea and test and information of conclutin stages. Reflective thinking process in solving mathematical problems in terms of assimilator learning style has not been carried out well because it does not carry out the rational elaboration of an idea and test and information of conclutin stages. The process of reflective thinking in solving mathematical problems in terms of converger learning styles is done well. Students with the learning style accommodator are not afraid to try new things. Students with the diverger learning style are individuals who get bored quickly when faced with a slightly complicated problem. Students with the assimilator learning style are individuals who observe and think a lot. Students with the converger learning style are individuals who have good abilities in problem solving and decision making.